Teacher disequilibrium, programmatic doublespeak, and "a day without immigrants". Issue 4 (2nd October 2022) - Salas, Spencer; Acosta, Jatnna; La Serna, Jillian
Abstract: In this article, we leverage in-depth interview to probe a Third Grade teacher's memories of the 2016–2017 School Year in a Spanish/English Dual Language Immersion (DL/I) school serving one of North Carolina's new Latinx communities. As our analysis will demonstrate, Mariana Castillo's interaction with the events of SY 16-17 combined with her still vivid memories as a child immigrant, led to her generalization that she was just another Brown body in the North Carolina piedmont—highlighting the emotional disequilibrium of teaching in the New Latino South and the unresolved tensions that social justice-equity oriented DL/I Latinx educators face when the branding of a state-led program is "instrumental/neoliberal oriented."